The implementation of third party endorsement as knowledge repository agent for creating trust in Malaysian's electronic banking industries - Kasiran, Mohd Khairudin; Ahmad, Faudziah; Meziane, Farid (2006)
Internet banking is a faceless banking arrangement where trust is still a major problem.This problem has been addressed through the implementation of third party endorsement on the bank's Websites.This endorsement acts as a knowledge repository on several issues about the bank's Websites.This paper intends to look on the current implementation of third party certification in Malaysian bank websites.Among the basic issues that will be discussed in this paper are the number of websites that has these endorsement, purpose of the endorsement, parties that provide the endorsement and the credibility of the endorsement.